The Influence of Teamwork, Competence, and Job Satisfaction on Productivity with Job Placement as a Mediating Variable: A Case Study in the Sample Room Division of the Garment Industry at PT. Mod - Rita, Rita Mariyana; Rakhman, Muhammad Arif; Nurmiyati, Nurmiyati (Amkop Management Accounting Review (AMAR), 2026)
The effectiveness of job placement is a critical issue in human resource management, particularly in ensuring alignment between individual competencies and job requirements. However, in practice, misalignment in job placement frequently occurs due to insufficient consideration of factors such as competence, teamwork, and work productivity. This study aims to analyse the influence of competence and teamwork on job placement, with productivity serving as the mediating variable. This study employs a quantitative approach with an explanatory research design. The population comprises all employees at the organisation under study, using a saturated sampling technique (census). Data were collected via a questionnaire using a Likert scale and analysed using Partial Least Squares (PLS)-based Structural Equation Modelling (SEM). The results indicate that competence has a positive and significant effect on productivity, and that teamwork also has a positive effect on productivity. Furthermore, productivity has a significant effect on job placement. Competence is the most dominant factor influencing job placement, followed by teamwork. Additionally, productivity was found to act as a mediating variable in strengthening the relationship between competence and teamwork on job placement. These findings indicate that improving the effectiveness of job placement requires strengthening competencies, enhancing teamwork, and optimising productivity as a mediating mechanism. This study contributes to the development of human resource management, particularly regarding the role of human capital and individual-job fit in enhancing organisational performance.